Β-Arrestin1 promotes the self-renewal of the leukemia-initiating cell-enriched subpopulation in B-lineage acute lymphoblastic leukemia related to DNMT1 activity. Issue 1 (1st February 2015) - Shu, Yi; Zhou, Xiaoyan; Qi, Xinkun; Liu, Shan; Li, Kang; Tan, Junjie; Liu, Zhidai; Yu, Jie; Zhang, Penghui; Zou, Lin
Hightlights: β-Arrestin1 is elevated in LICs from B-ALL. β-Arrestin1 enhances the self-renewal of LICs from B-ALL. The activity of DNMT1 is essential for the self-renewal of LICs from B-ALL. β-Arrestin1 promotes the activity of DNMT1, thus reduces the expression of PTEN in LICs from B-ALL. Abstract: The self-renewal ability of the leukemia initiating cell-enriched subpopulation is critical for leukemia initiation and maintenance. However, the regulation of leukemia initiating cells for the leukemia progression is poorly understood. In this study, we observed that β-Arrestin1, a multiple-function protein, is elevated in leukemia initiating cells-enriched fraction from B-lineage acute lymphoblastic leukemia patients. The loss of β-Arrestin1 in leukemia initiating cells-enriched fraction attenuates its self-renewal capacity both in vitro and in vivo . Further experiments showed that the mRNA expression level of β-Arrestin1 is negatively correlated with that of PTEN in leukemia initiating cells-enriched fraction. Moreover, DNA methylation of the PTEN promoter region, the activity and expression of DNMTs were enhanced in the leukemia initiating cells-enriched fraction. The inhibition of DNMT1 activity impaired the self-renewal and increased expression of PTEN of leukemia initiating cells-enriched fraction. In addition, depletion of β-Arrestin1 significantly decreased DNMT1 activity and PTEN methylation, and consistently increased PTEN expression in leukemia initiating cells-enriched fraction. Our study reveals a novel function of β-Arrestin1 in the regulation of the self-renewal of leukemia initiating cells-enriched fraction from B-lineage acute lymphoblastic leukemia patients related to DNMT1 activity, indicating that β-Arrestin1 is a potential therapeutic target in B-lineage acute lymphoblastic leukemia.